2014
DOI: 10.1007/s11064-014-1407-y
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Neuropathic Pain by Saikosaponin a in a Rat Model of Chronic Constriction Injury

Abstract: Despite immense advances in the treatment strategies, the effective treatment of patients suffering from neuropathic pain remains challenging. Saikosaponin a possesses anti-inflammatory activity. However, the role of saikosaponin a in neuropathic pain is still unclear. Therefore, the objective of this study was to investigate the effects of saikosaponin a on neuropathic pain. Neuropathic pain was induced by chronic constriction injury (CCI) of the sciatic nerve in rats. After CCI, rats were administered saikos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…They contribute significantly to the pharmacological activities of B. falcatum in vitro and in vivo , including anti‐inflammatory, immunomodulatory, anti‐tumor and hepatoprotection activities. In addition, in line with our results, saikosaponin A was shown to alleviate mechanical hypersensitivity in an animal model of chronic constriction injury (CCI)‐induced neuropathic pain (Zhou et al, ). Although the authors suggested that the reduced mechanical hypersensitivity is likely to be attributable, in part, to the anti‐inflammatory effects of saikosaponin A, we cannot exclude the possibility that TRPA1 antagonism by saikosaponin A also contributes to reducing CCI‐induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 87%
“…They contribute significantly to the pharmacological activities of B. falcatum in vitro and in vivo , including anti‐inflammatory, immunomodulatory, anti‐tumor and hepatoprotection activities. In addition, in line with our results, saikosaponin A was shown to alleviate mechanical hypersensitivity in an animal model of chronic constriction injury (CCI)‐induced neuropathic pain (Zhou et al, ). Although the authors suggested that the reduced mechanical hypersensitivity is likely to be attributable, in part, to the anti‐inflammatory effects of saikosaponin A, we cannot exclude the possibility that TRPA1 antagonism by saikosaponin A also contributes to reducing CCI‐induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 87%
“…Another study also found that NLRP3 mitigated injury to the pancreas and lungs, the inflammatory response and neutrophil infiltration in NLRP3 -/-SAP mice (45). Similar results were observed in a rat model of chronic constriction injury, where SSa inhibited the levels of TNF-α, IL-1β and IL-2 and reduced the elevated expression of MAPK and NF-κB in the spinal cord, thus attenuating neuropathic pain (46).…”
Section: Discussionsupporting
confidence: 63%
“…It inhibits the activation of p38 MAPK, NF- κ B signaling pathways to attenuate neuropathic pain (Zhou et al. 2014 ), and activates γ -aminobutyric acid (GABA) receptor B to attenuate cocaine-reinforced behavior (Yoon et al. 2012 , 2013 ) and drug addiction (Maccioni et al.…”
Section: Ssamentioning
confidence: 99%
“… 2014 ), and neuromodulation activities (Zhou et al. 2014 ). All of these potent effects are due to its various secondary metabolites, especially saikosaponins, the content of which is up to 7% of the total dry weight of Radix Bupleuri roots (Ashour & Wink 2011 ).…”
Section: Introductionmentioning
confidence: 99%